INTERNAL CASH FLOWS, INSIDER OWNERSHIP, INVESTMENT OPPORTUNITY, DAN CAPITAL EXPENDITURES: SUATU PENGUJIAN TERHADAP HIPOTESIS PECKING ORDER DAN MANAGERIAL - Hamidi, Masyhuri (Journal of Indonesian Economy and Business, 2003)
The objectives of this study are to observe the impact of internal cash flows, insider ownership, and investment opportunity on the capital expenditure in two different theories. Those theories are: (1) the pecking order hypothesis and (2) the managerial hypothesis, tested in Indonesian case.On the one hand, the pecking order hypothesis postulates that managers can choose the level of capital expenditure to maximize the wealth of current shareholders without considering insider ownership in the company. On the other hand, according to the managerial hypothesis, managers whose ownership proportions are small tend to use higher level of internal cash flows to finance the capital expenditure than that which would maximize the wealth of current shareholders.This study is predicated on Griner and Gordonâs study (1995) and focused on manufacturing companies listed in BEJ. The data used in this study are taken from the period of 1993-1996. There are 64 companies chosen based on purposive sampling.The result of this study shows that the internal cash flows and the investment opportunity have positive and significant impact on the capital expenditures. However, the impact of insider ownerships on the capital expenditures is not significant. Eventually, this study substantiates the pecking order hypothesis.Keywords: Pecking Order Hypothesis, Managerial Hypothesis, Internal Cash Flows, Insider Ownership, Investment Opportunity, Capital Expenditures